Baseline respiratory quotient predicts weight change in overweight and obese young women - Boschi, V.; Matrone, G.; Falcone, C.; Siervo, M. (Progress in Nutrition, 2007)
Background/Aims: The identification of behavioural and metabolic risk factors of weight gain is a continuous challenge. This study wants to assess the predictive value of non-protein respiratory quotient (NPRQ) and resting energy expenditure (REE) on changes of body weight after a 3 years follow-up in overweight and obese young women. Methods: Thirty-four women of age 25.7±5.8 years and BMI of 31.06±3.72, which were measured weight, height, body composition, resting energy expenditure and nonproteic respiratory quotient, started a weight loss programme and they attended individual, monthly follow-up visits for an average time of 7 months. After 36 months from baseline, subjects were contacted and invited to the clinic for a set of new measurements. Results: After 36 months weight change (weight loss) was 3.08±9.8 kg. The NPRQ showed a significant increase at the follow up (p